The Role and Characteristics of State Investment Policy in Contemporary Economic Relations - Kalantaryan, Vardan (ՀՀ ԳԱԱ)
The investment policy of the state plays an important role in the regulation and promotion of economic activity. The importance of developing a consistent and effective state investment policy is justified by the emergence of challenges and growing risks that disrupt the normal course of the modern economy from time to time, disrupting the flows of global investments. Accordingly, under such conditions, investments flow to countries where there is a favorable investment environment and an effective investment policy is conducted by the government. In crisis situations in particular, it is especially important to support investments towards productions utilizing modern innovative technologies, which will further contribute to the technological transformation of the country’s economy and its progressive growth. The main principle of the state policy towards private investors is, without interfering in their activities, to maximally contribute to the formation of the necessary legislative framework for increasing their investment activity and reliable protection of the invested funds. At the same time, special attention is paid to creating economic conditions for increasing the share of long-term investments in the non-state sector of the economy, as well as expanding the practice of attracting capital from private investors for the implementation of effective state programs. Պետության ներդրումային քաղաքականությունը կարեւոր դեր է խաղում տնտեսական գործունեության կարգավորման եւ խթանման գործում։ Պետության հետեւողական եւ արդյունավետ ներդրումային քաղաքականության մշակման կարեւորությունը հիմնավորվում է ժամանակակից տնտեսության բնականոն ընթացքը ժամանակ առ ժամանակ խաթարող մարտահրավերների եւ աճող ռիսկերի ի հայտ գալով, որոնք խաթարում են համաշխարհային ներդրումների հոսքերը։ Նման պայմաններում ներդրումները հոսում են դեպի այն երկրներ, որտեղ գործում է բարենպաստ ներդրումային միջավայր եւ կառավարության կողմից վարվում է արդյունավետ ներդրումային քաղաքականություն: Մասնավորապես, ճգնաժամային իրավիճակներում հատկապես կարեւորվում է այն տնտեսավարող ընկերություններին աջակցումը, որոնք ներդրում են կատարում ժամանակակից նորարարական տեխնոլոգիաներով արտադրություններում, ինչը հետագայում նպաստելու է երկրի տնտեսության տեխնոլոգիական վերափոխմանը եւ տնտեսության առաջանցիկ աճին: Инвестиционная политика государства играет важную роль в регулировании и стимулировании экономической деятельности. Важность выработки последовательной и эффективной инвестиционной политики государства обосновывается появлением вызовов и ростом рисков, которые время от времени нарушают нормальный ход современной экономики, нарушая потоки глобальных инвестиций. Соответственно, в таких условиях инвестиции перетекают в страны, где существует благоприятная инвестиционная среда и правительство проводит эффективную инвестиционную политику. В частности, в кризисных ситуациях особенно важна поддержка тех экономических компаний, которые инвестируют в производства с современными инновационными технологиями, что в дальнейшем способствует технологической трансформации экономики страны и поступательному росту экономики. Эффективная государственная инвестиционная политика направлена на активизацию инвестиционных процессов, обеспечение экономической стабильности и развития, формирование эффективных механизмов привлечения иностранных инвестиций и обеспечение их эффективной работы.
Keywords: State investment policy